The Translation of Islamic Rituals in the Novel Rimba Harapan into French: (Terjemahan Ritual Islam dalam Novel Rimba Harapan kepada Bahasa Perancis) (Malay Literature, 2019)
Religious elements are cultural aspects that often pose a problem in translation due to the fact that certain religious elements can only be fully understood by the people who practice the religion. If these religious elements need to be conveyed to a group of readers who have different beliefs and who use a different language, the translator needs to find a suitable mechanism in order to transmit these religious elements to the reader. In view of this, the aim of this study is to determine how Islamic rituals found in the novel Rimba Harapan [Jungle of Hope] are translated into French. To carry out the study, Islamic rituals in the novel were first identified. Each Islamic ritual was then mapped to its equivalent in the French translation. Next, the data collected in the form of Malay-French word pairs was analysed using the framework of translation procedures proposed by Franco Aixelá (1996). The analysis carried out revealed a total of 31 Islamic rituals in the Malay novel. An analysis of the Malay-French word pairs shows that the translator used both techniques-retention and substitution-in the process of translating. Through the use of both techniques, it can be concluded that the translator attempted not only to retain the originality of the source text, specifically through retention, but also to ensure that the target readers are able to fully understand the translation, specifically through substitution.Keywords: Cultural elements, religious rituals, Islam, translation procedures, Malay literature